Long Term Quality of Life Outcomes Following Surgical Resection Alone for Benign Paediatric Intracranial Tumours. (1st October 2022) - Kumar, Siddhant; Islim, Abdurrahman; Moon, Richard; Millward, Christopher; Hennigan, Dawn; Bakhsh, Ali; Thorpe, Antonia; Foster, Mitchell; Pizer, Barry; Mallucci, Conor; Jenkinson, Michael
Abstract: AIMS: Survivors of paediatric intracranial malignancies are at increased risk of psychosocial, neuro-developmental and functional impairment, important measures of patients' well-being. This study aimed to evaluate long-term quality of life outcomes (QOL) in patients with benign paediatric brain tumours treated curatively with surgical resection alone. METHOD: Cross-sectional cohort study of benign paediatric intracranial tumours managed with surgery alone between 2000-2015. Validated QOL questionnaires were administered: SF-36, QLQ-BN20, QLQ-C30 and PedsQLTM. RESULTS: Twenty-three patients participated (median age at surgery 13 years; range 1-18), twelve were male. The most common diagnosis was pilocytic astrocytoma (n=15). Median time from surgery to participation was 11 years (range 6-19). Fourteen patients achieved A-level qualifications and two obtained an undergraduate degree. Twelve patients were employed, eight were studying and three were unemployed or volunteering. Twelve patients were currently driving. QOL outcomes demonstrated significant limitation from social functioning (p=0.03) and cognitive functioning (p=0.023) compared to the general population norms. Patients also experienced increased loss of appetite (p=0.009) and symptoms of nausea and vomiting (p=0.031). Ten patients were under transitional teenager and young-adult (TYA) clinic follow-up. TYA patients achieved higher levels of education (p=0.014), were more likely to hold a driver's license (p=0.041) and had improved physical functioning (p=0.005) compared to patients not transitioned through these services. CONCLUSION: Childhood brain-tumour survivors are particularly vulnerable and at greater risk of developing psychological, neuro-cognitive, socialisation and physical development challenges. Early identification, comprehensive assessment and specialist TYA cancer healthcare input are vital to support these patients and improve their quality of life.